Dishonesty and Risk-Taking: Compliance Decisions of Individuals and Groups - Martin Fochmann; Martin G. Kocher; Nadja Müller; Nadja Wolf (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2019)
Unethical behavior in organizations is usually associated with the risk of negative consequences for the organization and for the involved managers if being detected. The existing experimental literature in economics has so far mainly focused on the analysis of unethical behavior in environments that involve no fines or similar monetary consequences. In the current paper, we use a tax compliance framework to study (un-)ethical behavior of individuals and small groups. Our results show that groups are clearly less compliant than individuals. The risk of being detected is the most important aspect in the group communication process when deciding on compliance.
Keywords: C91; C92; D03; H26; 330; Dishonesty; lying; compliance; risk-taking; group decisions; communication; norms; experiment